Gm40600 promotes CD4+ T‐cell responses by interacting with Ahnak. Issue 1 (2nd June 2021) - He, Youdi; Fang, Ying; Zhai, Bing; Liu, Xiaoling; Zhu, Gaizhi; Zhou, Shan; Xu, Yaqi; Wang, Xiaoqian; Su, Wenting; Wang, Renxi
Abstract: It is important to characterize novel proteins involved in T‐ and B‐cell responses. Our previous study demonstrated that a novel protein, Mus musculus Gm40600, reduced the proliferation of Mus musculus plasmablast (PB)‐like SP 2/0 cells and B‐cell responses induced in vitro by LPS. In the present study, we revealed that Gm40600 directly promoted CD4 + T‐cell responses to indirectly up‐regulate B‐cell responses. Importantly, we found that CD4 + T‐cell responses, including T‐cell activation and differentiation and cytokine production, were increased in Gm40600 transgenic (Tg) mice and were reduced in Gm40600 knockout (KO) mice. Finally, we demonstrated that Gm40600 promoted the Ahnak‐mediated calcium signalling pathway by interacting with Ahnak to maintain a cytoplasmic lateral location of Ahnak in CD4 + T cells. Collectively, our data suggest that Gm40600 promotes CD4 + T‐cell activation to up‐regulate the B‐cell response via interacting with Ahnak to promote the calcium signalling pathway. The results suggest that targeting Gm40600 may be a means to control CD4 + T‐cell‐related diseases. Abstract : Gm40600 in B cells suppressed GC B‐cell responses and antibody production. However, Gm40600 in T cells promoted CD4 + T cell responses to indirectly up‐regulate GC B‐cell responses and antibody production. Furthermore, Gm40600 promoted CD4 + T‐cell activation to upregulate B‐cell responses via interacting with Ahnak to promote the calcium signaling pathway in CD4 + T cells. These results provide a hint for targeting Gm40600 to control CD4 + T‐cell‐related diseases.